KARYA KARAWITAN BARANG MIRING - Sosodoro, Bambang (Institut Seni Indoensia Surakarta, 2009)
Barang Miring music composition is inspired by the musical gamelan of sekaten, a set of ancient ensamble called Kyahi GunturMadu and Kyahi Guntur Sari of Surakarta Palace. This unique musical gamelan is often used by compÃ©sers in their creations. It has also been using sources of creation, creative materials, creativity approach, imitation, etc. Gamelan itself generally accompanies other performance like dance, puppet show, and even the gamelan performance itself Based on this phenomenon 1 would like to examine a gamelan Sekaten as an object of material. Through this article I present the musical creation based on gamelan sekaten tradition and actualize through the new creation called Barang Miring. gendhing Barang Miring of gamelan sekaten will be the main sources because of its uniqueness as a major repertoire of gamelan sekaten. It is performed traditionally after the Adzan Asyhar when the Moslem does their sholat. This article also strive a reason of what kind of concept of Barang Miring (minur) into the concept of gamelan ageng performance. Using reinterpretation approach based on traditional repertoire, this article exists as a representation of a new field of creation in music creation based on karawitan traditional composition.Â Key words: barang miring, musiccreation, gamelan sekaten,